CONTROL OF ECTOPARASITIC MITE VARROA DESTRUCTOR IN HONEYBEE (APIS MELLIFERA L.) COLONIES BY USING DIFFERENT CONCENTRATIONS OF OXALIC ACID - M. Rashid; E. S. Wagchoure; A. U. Mohsin; S. Raja; G. Sarwar (Journal of Animal and Plant Sciences, 2012)
The research work was carried out to determine the effects of oxalic acid (OA) on reducing ectoparasitic mite Varroa destructor Anderson and Trueman (Acari:Varroidae) populations in honeybee Apis mellifera linguistica (Hymenoptera: Apidae) colonies in the fall at Honey bee Research Institute, National Agricultural Research centre, Islamabad. Twenty honeybee colonies were used in this experiment. Colonies were divided into four groups of five colonies each. Oxalic acid was applied in sugar syrup with 4.2, 3. 2 and 2.1% concentrations. The OA with different concentrations was tricked directly on the adult honey bees in between two frames using a syringe applied thrice on different dates at five days interval. Average efficacy of OA with 3.2, 4.2 and 2.1 % was 95, 81 and 46 % respectively. No queens were lost, and there was no adult honeybee mortality in any of the colonies during the experiment. It can be concluded that 3.2% OA concentration are very effectively control varroa mite and can be used without any side effect during broodless condition.
Keywords: Honeybee; Varroa destructor; oxalic acid; trickling.